إجراءات تنفيذ الأحكام القضائية الصادرة ضد الإدارة العمومية المتضمنة إلتزام مالي - بوصبيع, صالح شافعي; تجاني, عبد الحافظ (University of Eloued جامعة الوادي, 2022)
ويثير تنفيذ الأحكام القضائية النهائية أهمية كبيرة، إذ لا معنى لهذه القرارات والأحكام، إذا لم يستطيع صاحب الحق استفاءة فعلا بتنفيذ الحكم. غير انه من الملاحظ أن بعض الأحكام الصادرة ضد الجهات الإدارية وخاصة المتضمن التزام مالي لا تجد طريقها إلى التنفيذ بسبب امتناع الجهات الإدارية، ورغم الحلول الجزئية التي أوجدتها بعض الأنظمة و كذلك الدساتير منها التعديل الدستوري الجزائري 2020, المنشور ج.ر, عدد 82, الصادرة بتاريخ 30/12/2020 لا زال عدم الامتثال الإدارة للإحكام الصادرة ضدها نقطة ضعف في القانون الإداري. فأحكام القضاء الصادرة ضد الإدارة بصفة عامة تصدر بعد إجراءات متعددة واستعمال مختلف الطعون وبمشاركة مجموعة من المتدخلين من أطراف قضائية وشبه قضائية مثل وسيط الجمهورية. بناءا على ما سبق تقع دراسة هذا البحث على مقدمة و فصلين و خاتمة, حيث يتضمن الفصل الأول التنفيذ الاختياري للحكم القضائي الإداري المتضمن التزام مالي ضد الإدارة و الذي ينقسم إلى مبحثين بحيث تناولنا في المبحث الأول التنفيذ الاختياري طبقا لقانون الإجراءات المدنية والإدارية و في المبحث الثاني التنفيذ عن طريق وسيط الجمهورية. و تطرقنا في الفصل الثاني التنفيذ الجبري للحكم القضائي الإداري المتضمن التزام مالي ضد الإدارة و الذي بدوره ينقسم إلى مبحثين, تناولنا في المبحث الأول صور التنفيذ الجبري أما في المبحث الثاني تناولنا المسؤولية المترتبة عن عدم الامتثال لإجراءات التنفيذ. The execution of final judgments plays a major role so, they are meaningless if the right holder could not benifits after the execution.nevertheless it is noticeble that some verdicts against administrative authorities, especialy those included a financial commitement never been executed due to administrative authorities refrain. Despite of the partial solutions set by some systems and constitutions, such as the 2020 Algerian constitution reform, published in the official journal n°82 released December,30,2020. The administration authorities refrain of verdicts execution still considered as a virtual Achilles heel of administrative law. In general, the verdicts against the administration issued after a long journey of proceedings including variety of appeals, with the participation of involved parties ; judicial parties such as the Mediator of the Republic. Based on what preceeded, the present study required an introduction and two Chapters in addition to a Conclusion, in the first hand, the First Chapter will deal with the optional execution of judicial judgments included financial commitments against the administration, which divided into two sections, the first one tackeled the optional execution in light of the civil code of procedures and administrative. While the second section is going to deal with the execution through the Mediator of the Republic. In the other hand, the second Chapter sheds light on the mandatory execution of judicial administrative judgments which, includes a financial commitment against the administration, also divided into two sections. The first section dealt with the ways of mandatory execution, while in the second section we tackeled the incured responsibility due to execution procedures refrain
مدكرة ماستر
Keywords: التنفيذ- الأحكام القضائية الإدارية - التنفيذ الاختياري - التنفيذ الجبري - إدانة مالية - المسؤولية الإدارية - وسيط الجمهورية; Administrative judicial verdicts, optional execution, mandatory execution, administrative responsibility, mediator of the republic, financial accusation.